ANALISIS PERANCANGAN SISTEM INFORMASI GEOGRAFISUNIT KERJA PRESIDEN BIDANG PENGAWASAN DAN PENGENDALIAN PEMBANGUNAN - Rayi Indrarinardi, (2014)
Rayi Indrarinardi, S.ST., NPM 112.0921.089, thesis titled: "Design Analysis of Geographic Information System of President's Delivery Unit for Development Monitoring and Oversight" to attain a Master Degree of Information System Management in Post-Graduate Program of Universitas Pembangunan Nasional "Veteran" Jakarta. In developing the monitoring function, the President's Delivery Unit for Development Monitoring and Oversight (known as UKP-PPP) relies on information technology in its daily work to analyze and solve development problems, including the use of geographic information systems that are provided by Ministries or Agencies. Normally, each institution has their own thematic data in their system. For example, Ministry of Health provides their health facilities data around the country and The National Disaster Management Agency provides their monitoring of disasters data. Once the disaster occures, those information could be visualized in each geographic information system application that allows UKP-PPP users to analyze how many victims caused by the disaster, where the nearest health facilities is, how fast they could get health services, and so on. Furthermore, UKP-PPP also possesses their own geospatial visualization system to visualize and report their field monitoring activities to get the real information that could be found in the location and to show the real conditions that happened. Based on that case, the UKP-PPP analysts use at least three different applications, with different interfaces and different features of applications many times until they have finished their analysis. It indicates that using many types of thematic data would lead to raise effective processing. Geographic information system has designed by focused on users' needs that could give them simplicity in using more than one type of thematic data, using qualitative research methodology by placing the prospective users as informants. This type of geographic information system integrates many types of thematic data into single view. Users could use this system to assist them in spatial-based analyzing and get solution of the problems and to support the decision maker in providing the best outcomes. To convince the UKP-PPP leader that this geographic information system could be implemented, this research also arrange implementing strategies based on internal and external factors through SWOT analysis. The results meet significantly what has been hypotized